2019
DOI: 10.1038/s41598-019-43601-z
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial hydrogen atoms in face-centered cubic iron in the Earth’s core

Abstract: Hydrogen is likely one of the light elements in the Earth’s core. Despite its importance, no direct observation has been made of hydrogen in an iron lattice at high pressure. We made the first direct determination of site occupancy and volume of interstitial hydrogen in a face-centered cubic (fcc) iron lattice up to 12 GPa and 1200 K using the in situ neutron diffraction method. The transition temperatures from the body-centered cubic and the double-hexagonal close-packed phases to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 27 publications
10
49
3
2
Order By: Relevance
“…The latest NPD study of Fe hydride revealed that the γ-ε′phase boundary was located at temperatures 100-200 K higher than those shown in Fig. 1 19 , and the appearance of the dhcp deuteride at 673 K and 6.1 GPa was consistent with the latest result. The formation of the metastable hcp phase was sensitive to the cooling rate; a larger amount of the hcp deuteride formed at a faster cooling rate 18 .…”
Section: Resultssupporting
confidence: 82%
“…The latest NPD study of Fe hydride revealed that the γ-ε′phase boundary was located at temperatures 100-200 K higher than those shown in Fig. 1 19 , and the appearance of the dhcp deuteride at 673 K and 6.1 GPa was consistent with the latest result. The formation of the metastable hcp phase was sensitive to the cooling rate; a larger amount of the hcp deuteride formed at a faster cooling rate 18 .…”
Section: Resultssupporting
confidence: 82%
“…As the most abundant element in the universe, hydrogen is one of the candidates. Although its solubility in iron at atmospheric pressure (P) is very limited, the affinity of hydrogen to iron increases significantly under compression (Antonov et al, 1998;Badding et al, 1991;Fukai, 1984) as the Gibbs energy (G) of gaseous hydrogen increases rapidly with P. Solution of hydrogen in iron has been confirmed by neutron diffraction measurements (Ikuta et al, 2019;Machida et al, 2014) at high P, with H dissolving interstitially in Fe, expanding the lattice in a systematic way. The affinity to iron (siderophile behavior) at high P suggests that hydrogen is a strong candidate for the light element in the core.…”
Section: Introductionmentioning
confidence: 99%
“…The EPMA analyses and the H contents are summarized in Table 1. The error in H concentration may be ±8%, which is derived mainly from uncertainty in DVH 9,28 .…”
Section: Sample Analysesmentioning
confidence: 99%
“…Fcc stoichiometric FeH included the least amounts of Si when coexisting with Fe-Si-H liquids (Fig. 3a), suggesting that Si atoms do not substitute Fe when octahedral interstitial sites are fully occupied by H atoms 28 . On the other hand, the chemical composition of the B2 phase formed in run #1 was estimated to be (Fe0.77Si0.23)H0.4, which is enriched in both Si and H than hcp (Fe0.93Si0.07)H0.25 found in run #4.…”
Section: Solid-liquid Partitioning Of Si and H The Solid/liquid Partition Coefficients Of Si And Hmentioning
confidence: 99%
See 1 more Smart Citation